REASONS FOR PEOPLE IN LAW BRINGING AN ATTORNEY AND THEIR ROLES IN ACCOMPANYING CLIENTS: Case Study of Marriage Cases in Jember Religious Court - Teguh Dwi Cahyadi; Adi Gunawan (Al-Usariyah: Jurnal Hukum Keluarga Islam, 2023)
In proceedings at a religious court, someone who is litigating will experience difficulties in the proceedings. This is because the proceedings and legal rules in religious courts are complicated, so a person needs a lawyer to ask for legal assistance in proceedings at a religious court. However, the reason why a person brings an attorney in a religious court needs to be studied further to find out the reasons why litigants bring attorneys in a religious court and their role in accompanying their clients in religious courts. This research is a field research conducted at the Jember Religious Court using a qualitative approach. The results of this study indicate that the reason someone brings attorneys to Jember Religious Court is a lack of knowledge of law, the complexity of the proceedings at the Religious court, someone who is in a case wants to get a satisfactory result, and someone who is having a case is busy with his livings and work. The role of attorneys in accompanying clients at the Jember Religious Court is to represent clients, to cause the ligitants to be present, to provide legal advice to clients, to assist with case administration, to provide legal services to clients, and to defend client interests. Keywords: attorney, religious court, litigation reason